Otimização do comportamento térmico de edificações industriais: estudo de caso em indústria metalomecânica na Zona Bioclimática Brasileira 2 - Garlet, Liége (2017)
Commitment to providing thermally comfortable working environments is one of the key aspects for workers to raise their performance. To achieve this goal, sometimes, high energy consumption is required. In this sense, this work intends to test the feasibility of the application of bioclimatic strategies for the reduction of energy expenditure and improvement of thermal comfort in industrial pavilions of the metal-mechanical sector, installed in the Brazilian Bioclimatic Zone 2, through studies of the thermal behavior of a case study, with the adoption of two analytical methodologies. One of them, for the industrial pavilion, naturally ventilated, analyzing the thermal comfort conditions of its users with the adaptive method. The other, for the office building, which is artificially cooling, using the prescritive and simulation method of the RTQ-C, evaluating the energy efficiency of this building. We also analyzed the thermal flows of both buildings, that is, their thermal behavior, verifying where the main losses and the heat gains occurred in the buildings. The analysis of thermal flows of the industrial pavilion highlighted the high heat gains through walls and roof in summer and winter and the expressive losses by infiltration. Analyzed the proposals of bioclimatic solutions for the pavilion, it was verified that the most appropriate are the use of controlled ventilation and with the isolated roof and the low solar absortance of walls and roofs. In the diagnosis of the sensation of thermal comfort for the hours occupied, from the solutions that best stood out, the percentage of hours in comfort of 12.81% was increased considering solutions to ameliorate cold and heat, with possibility of reduction of the heat discomfort by 57%. At the office, the RTQ-C evaluation pointed to the D-level classification of the building in the two evaluated methods, and the analysis of the thermal flows detected a large internal heat generation from the equipment, lighting and occupation, as well as gains from windows and walls in summer, and significant losses through the windows, walls and roof in winter. Tested proposals for solution to the office, identified as the most feasible the replacement of light bulbs by the equivalents of lower consumption, the suitability of the setpoint of air conditioners, the use of low solar absortance of the envelope and the use of external sunscreens, achieving a reduction of 48.36% in energy consumption. The general analysis of the buildings reflect the main modifications to be considered, which are design issues and can be solved following the concepts of bioclimatic architecture, in which the envelope should facilitate the loss of heat and / or impede its entry, as well as the choice of equipment that consumes less energy is decisive for the energy efficiency of the building.